Cdc25A-Driven Proliferation Regulates CD62L Levels and Lymphocyte Movement in Response to Interleukin-7 - Kittipatarin, Christina (2010)
OBJECTIVE: IL-7 is a multifunctional cytokine and a promising immunotherapeutic agent. However, since a transient T-cell depletion is an immediate outcome of IL-7 administration at supraphysiological doses, we investigated the mechanism by which the IL-7 proliferative signal transduced through Cdc25A, a key activator of cyclin dependent kinases (CDKs), could modulate lymphocyte movement. METHODS: Employing novel methods of manipulating Cdc25A gene expression, combined with in vitro and in vivo evaluation of IL-7 application, we assessed the expression of activation and homing markers and identified the mechanism by which IL-7 could induce T-cell expansion and alter lymphocyte motility. RESULTS: Constitutively active Cdc25A drove T-cell proliferation independently of IL-7 and resulted in an activated phenotype (CD69(hi), CD44(hi)). Conversely, inhibition of Cdc25A resulted in decreased proliferation, reduced expression of activation markers and the up regulation of the lymph node homing molecule, CD62L, which promoted cell adhesion when engaged by ligand. We found that IL-7 prevented the nuclear translocation of the transcription factor, Foxo1, in a manner dependent on the activity of Cdc25A, resulting in decreased levels of CD62L. In vivo administration of IL-7 decreased lymph node cellularity, while treatment with IL-7, premixed with a neutralizing IL-7 antibody (M25), increased total lymph node cells – with more nuclear Foxo1 detected in cells from mice receiving IL-7 + M25. CONCLUSION: These results are consistent with the model that IL-7 drives Cdc25A-mediated T-cell proliferation, which prevents the nuclear translocation of Foxo1, leading to reduced expression of CD62L and the migration of T-cells into circulation.